Integrated cyclostratigraphy of the Cau core (SE Spain) - a timescale for climate change during the early Aptian Anoxic Event (OAE 1a) and the late Aptian - Martínez-Rodríguez, R; Batenburg, SJ; Castro, JM; de Gea, GA; Nieto, LM; Ruiz-Ortiz, PA; Robinson, S (Elsevier, 2024)
We report a cyclostratigraphic study performed on the Cau core (Spain), which is considered an Aptian stratigraphic reference for global correlation and paleoenvironmental reconstruction. This investigation presents an astronomical timescale for the Aptian from Ap2a to Ap14 carbon-isotope stages. Based on the evaluation of a multiproxy dataset from the Cau core, we recalibrate the age and duration of the different biozones, bioevents, chemostratigraphic substages and horizons from the early and late Aptian, with special focus on the Selli Event, providing a new astronomical timescale framework for the Aptian climate. From the recognition of 14 long-eccentricity cycles, we propose a time span of 5.67 Ma for the Ap2a to top of Ap14 C-isotope segments, and ages of 120.82 Ma for the onset of the nannoconid crisis, and 120.20 Ma for the onset of the oceanic anoxic event (OAE) 1a. Calculations yield a duration of 1.47 Ma for the OAE 1a. We estimate the age for the onset of the main Os isotope non-radiogenic phase as 120.08 Ma, 120 ka after the onset of the OAE 1a. The high-resolution data from the Cau core provides further insights in the temporal constraints of the OAE 1a and other Aptian paleoclimatic events. The onset of the main Os-isotope non-radiogenic excursion occurring 120 ka after the onset of the OAE 1a reinforces the theory of rapid destabilization of methane hydrates as the trigger of the anoxic event, that preceded the onset of large-scale volcanism.